3D Bioprinting in Medicine - Fulden Ulucan-Karnak (Global Journal of Biotechnology and Biomaterial Science - Peertechz Publications, 2021)
3D bioprinting of tissues and organs is game changer and promising technology in medicine. It has also great potential to be substitution of animal models as artificial tissue or organ platforms and can be used for transplantation to the patient directly. Natural and synthetic polymers can be used as bioinks in order to develop tissue or organ models and they can be applied from benches to clinical application. In this review, it is aimed to summarize 3D printing technology in medicine and bioinks.